2020
DOI: 10.1186/s12989-019-0334-0
|View full text |Cite
|
Sign up to set email alerts
|

Inhalation of welding fumes reduced sperm counts and high fat diet reduced testosterone levels; differential effects in Sprague Dawley and Brown Norway rats

Abstract: Background: Previous studies have shown that inhalation of welding fumes may induce pulmonary and systemic inflammation and organ accumulation of metal, to which spermatogenesis and endocrine function may be sensitive. Also obesity may induce low-grade systemic inflammation. This study aimed to investigate the effects on sperm production of inhaled metal nanoparticles from stainless steel welding, and the potential exacerbation by intake of a high fat diet. Both the inbred Brown Norway and the outbred Sprague … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 50 publications
0
9
0
Order By: Relevance
“…Furthermore, a recent study demonstrated that feeding a HFD from 12 to 24 weeks did not influence any of the motility parameters or the concentration of sperm in the epididymal cauda. 30 The current study aimed to reveal the short-term and cumulative effects of a HFD on sperm parameters. There was a trend of decreased sperm concentration after 42 weeks of exposure to a HFD, which is consistent with our previous work.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a recent study demonstrated that feeding a HFD from 12 to 24 weeks did not influence any of the motility parameters or the concentration of sperm in the epididymal cauda. 30 The current study aimed to reveal the short-term and cumulative effects of a HFD on sperm parameters. There was a trend of decreased sperm concentration after 42 weeks of exposure to a HFD, which is consistent with our previous work.…”
Section: Discussionmentioning
confidence: 99%
“…Higher testosterone levels may increase the risk of prostate cancer (28). Studies conducted in rats fed a high-fat diet have shown that it decreases androgen receptor and serum testosterone levels, potentially producing a protective effect (29). Furthermore, studies in obese men have found increased estrogen production and androgen clearance, which could also affect the development of prostate cancer (30).…”
Section: Discussionmentioning
confidence: 99%
“…This requires knowledge of the in vivo relevance of the sometimes relatively simple in vitro endpoints, and on how to extrapolate in vitro concentrations to in vivo kinetics. We must however also discuss animal studies as the gold standard for human hazard assessment, look into the consequence of strain differences in toxic response (Skovmand et al, 2020 ), and review how findings and hypotheses generated in animals and in vitro correlate with evidence in humans (Bonde et al, 2016 ).…”
Section: The Future Lies In Crosstalkmentioning
confidence: 99%